Why and How the Tobacco Industry Sells Cigarettes to Young Adults: Evidence From Industry Documents - Ling, Pamela M. (© American Journal of Public Health 2002, 2002)
Objectives. To improve tobacco control campaigns, we analyzed tobacco industry strategies that encourage young adults (aged 18 to 24) to smoke. Methods. Initial searches of tobacco industry documents with keywords (e.g., “young adult”) were extended by using names, locations, and dates. Results. Approximately 200 relevant documents were found. Transitions from experimentation to addiction, with adult levels of cigarette consumption, may take years. Tobacco marketing solidifies addiction among young adults. Cigarette advertisements encourage regular smoking and increased consumption by integrating smoking into activities and places where young adults' lives change (e.g., leaving home, college, jobs, the military, bars). Conclusions. Tobacco control efforts should include both adults and youths. Life changes are also opportunities to stop occasional smokers' progress to addiction. Clean air policies in workplaces, the military, bars, colleges, and homes can combat tobacco marketing. (Am J Public Health. 2002;92:908–916)